A Possible Distinct Molecular Subtype (Quintuple-Wildtype) of Metastatic Colorectal Cancer in First-Line Anti-EGFR Therapy with Cetuximab Plus FOLFIRI - Palliative Precision Therapy and a Multidisciplinary Treatment Approach: Interim Analysis of the IVOPAK II Trial with Early Results - Wein, Axel; Stöhr, Robert; Kersting, Stephan; Siebler, Jürgen; Merkel, Susanne; Busse, Daniel; Wolff, Kerstin; Ostermeier, Nicola; Neufert, Clemens; Vitali, Francesco; Eckstein, Markus; Roth, Jan-Peter; et al. (Oncology, 2021)
Objective: The study aimed to prospectively evaluate a new molecular biomarker panel (KRAS, NRAS, BRAF, PIK3CA, and ERBB2) for palliative first-line treatment of colorectal cancer (CRC), including a multidisciplinary treatment approach. The rate of secondary metastasis resections was assessed. Patients and Methods: A total of 40 patients with definitively nonresectable metastatic CRC were enrolled from 10 centers before the interim analysis (June 2019) of the IVOPAK II trial (Interdisciplinary Care with Quality Control in Palliative Treatment of Colorectal Cancer). After determination of 5 molecular biomarkers in the tumor (KRAS, exons 2-4; NRAS, exons 2-4; BRAF V600E; PIK3CA; and ERBB2), patients in the IVOPAK II study received FOLFIRI plus cetuximab for all-RAS/quintuple-wildtype disease and FOLFIRI plus bevacizumab in the case of RAS mutations. The current article presents the early description of the clinical outcome of the interim analysis of IVOPAK II comparing the all-RAS/quintuple-wildtype and RAS-mutations populations, including a multidisciplinary-treated case report of a quintuple-wildtype patient. Results: The quintuple-wildtype population treated with FOLFIRI plus cetuximab in first-line exhibited a significantly higher response rate and enhanced early tumor shrinkage in the interim analysis than the RAS-mutations population, as well as a high rate of secondary metastatic resections. Conclusion: Initial results of this new biomarker panel (quintuple-wildtype) are promising for anti-EGFR therapy with cetuximab plus doublet chemotherapy (FOLFIRI) in first-line treatment of metastatic CRC. These results warrant confirmation with higher case numbers in the IVOPAK II trial.
CRIS-Team WoS Importer:2021-11-05